On the Goal of Existentialist Therapy - Govedarica, Milanko J. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The author distinguishes between psychotherapy and philosophical therapy and understands existentialist therapy as a paradigmatic example of philosophical therapy. In this domain, the restriction to Sartre’s influence is explained by the need to reduce imprecise and eclectic speech on existentialist ideas in psychotherapy. Sartre’s philosophical starting points in his criticism of Freud’s psychoanalysis in promoting his own existential psychoanalysis concept are considered. The French existentialist appears to criticize Freud’s teaching due to overemphasizing the external causation of human behaviour, deeming human choices primary and that the meanings of all the external givenness result from them. It is shown that the need for existentialist therapy results from the experience of disrupted authenticity, that is, from the experience of unoriginality and futility of one’s own life. Thus, it is explained that the authenticity of existence does not imply abstract commitment to the chosen higher values, but their coordination with facticity, as well as that it includes not only the engagement for the meaning that can be obtained, but also the reconciliation with what is ontologically not possible to change. Among other things, the conclusions are drawn about the similarities between the goal of existentialist therapy and anti-psychiatric efforts, as well as regarding who should be the bearer of this type of therapeutics.